From means to end: Understanding the millennial mind when buying luxury jewelry brands - Ratakam P. (2023)
For those in the luxury fashion industry, the global fine jewelry market has rebounded from the effect of the COVID-19 pandemic due to the participation of millennials. Understanding the attitudes and values that drive millennials’ decision-making processes, as well as acquiring better knowledge of how their needs change, is essential to aid the survival of luxury brands. This research applied the means-end theory as a framework to explore millennials’ preferences regarding the product attributes, benefits, and values that drive purchasing decisions. Thirty Thai millennials participated in the hard laddering interviews. The means-end chains obtained were analyzed using the LadderUX software. Brand, product function, and beauty are the key attributes that drive the purchasing decision, as they have a stronger link to the top values–happiness and self-confidence–of the millennial mindset.